2020
DOI: 10.1017/ice.2020.1359
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effects of operating room staff movement and door opening policies on microbial load

Abstract: Objective: To identify factors that increase the microbial load in the operating room (OR) and recommend solutions to minimize the effect of these factors. Design: Observation and sampling study. Setting: Academic health center, public hospitals. Methods: We analyzed 4 videotaped orthopedic surgeries (15 hours in total) for door openings and staff movement. The data were translated into a script denoting a representative frequency and location of movem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Another article varied door opening time and width as part of its study design, and found that longer door openings led to a significant increase in number of CFU counts on both bacterial and combined microbial settle plates (bacteria and fungi combined). 55 This same study compared the width of the door opening at 45 versus 90 degrees and found that wider door openings lead to higher total CFU on combined settle plates. Two articles reported door size in addition to their results, but neither of these evaluated the impact of OR door size on particle counts or another relevant outcome.…”
Section: Operating Room Doorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Another article varied door opening time and width as part of its study design, and found that longer door openings led to a significant increase in number of CFU counts on both bacterial and combined microbial settle plates (bacteria and fungi combined). 55 This same study compared the width of the door opening at 45 versus 90 degrees and found that wider door openings lead to higher total CFU on combined settle plates. Two articles reported door size in addition to their results, but neither of these evaluated the impact of OR door size on particle counts or another relevant outcome.…”
Section: Operating Room Doorsmentioning
confidence: 97%
“…A total of 12 out of the 33 articles that discussed OR doors as they relate to airflow and contamination did not include recommendations following the results of their studies. 27,46,64,65,50,[53][54][55][56][57]62,63 Of the 21 articles remaining, five proposed recommendations that focused on altering specific behaviors of the OR staff. 7,[66][67][68][69] These recommendations included limiting unnecessary staff movement related to OR door openings, limiting the number and duration of door openings, and limiting the number of staff in the OR in general.…”
Section: Operating Room Doorsmentioning
confidence: 99%
“…Das Werkstück in einem industriellen Reinraum ist selbst schon rein und unbelebt, während im OP ein lebendes Wesen mit dem entsprechenden körpereigenen Mikrobiom behandelt wird. Man wird in der Industrie auch nicht erleben, dass die Türen zum Reinraum in Abständen von wenigen Minuten immer wieder geöffnet werden [2] Zu Schluss sei mal wieder an Joseph Lister erinnert, der schon 1890 aussagte, dass schwebende Partikel und Mikroben in der Luft außer Acht gelassen werden können, wenn sichergestellt werden kann, dass die Operateure keine septischen Verschmutzungen aus anderen Quellen in die Wunde hineintragen [3].…”
unclassified